Қазақстандағы атом электр станциясының салудағы мүмкіншіліктері. - Талжанов, С.А.; Еркін, М.П. (Академик Е.А. Бөкетов атындағы Қарағанды Университеті, 2025)
The article examines Kazakhstan's nuclear energy prospects, addressing electricity shortages, ecological goals, public concerns, infrastructure gaps, and nuclear medicine advancements, emphasizing the need for a comprehensive approach and public trust.
Современное состояние и перспективы развития географической науки Казахстана.
Keywords: comprehensive approach; public trust; nuclear medicine; infrastructure; seismic risks; radioactive waste; ecological commitments; electricity shortage; nuclear energy; АЭС; Атом электр станциясы; Қазақстан; энергетика саласы; модернизация; жаһандық экология; атом энергетикасы; референдум; Уран; Ядролық реактор; радиоактивті қалдықтар; Сейсмикалық белсенділік; изотоп; Радиофобия; радио-префикс; Ядролық медицина; ақпарат жетіспеушілігі; жаңа заман технологиялары